Two- and three-mode intensity-difference squeezing in cascaded four-wave mixing inside an optical cavity. (13th September 2019) - Jiang, Weiqi; Li, Xinghua; Mu, Fan; Mao, Jianyong; Liu, Yang; Zhang, Yanpeng
Abstract: We report a theoretical study about the two- and three-mode intensity-difference squeezing inside an atom-like optical cavity. A cascaded parametric amplification four-wave mixing process is considered, and the cavity dressing and 'dressing-like' effects with different nonlinear coefficients affecting the degree of squeezing of the fluctuation spectra are researched. The altering of the nonlinear coupling coefficient changes the relationship between the cavity dressing and 'dressing-like' effects, which determines the squeezing degree and results in a new type of multi-dip squeezing and double-peak anti-squeezing.